Pinch‐based shortcut method for the conceptual design of isothermal extraction columns. Issue 4 (5th October 2016) - Redepenning, Christian; Recker, Sebastian; Marquardt, Wolfgang
Abstract : Shortcut methods are valuable tools for a comprehensive evaluation of key performance indicators in the early phase of conceptual process design. For the design of extraction columns, operation at minimum solvent demand represents a thermodynamically sound indicator, which is, however, difficult to determine. The suggested shortcut model therefore exploits the existence of the pinch point to directly identify operation at minimum solvent demand. It is solved quickly and reliably by a step‐by‐step procedure. The final step allows a reduction of the approximation error to any desired degree of accuracy. No simplifications regarding the number of components in the mixture or its thermodynamic behavior are introduced. Hence, arbitrary mixtures can be tackled. The performance of the method is highlighted by a fully automated screening of thousands of solvents for the recovery of fermentation products acetone, 1‐butanol, and ethanol from aqueous solution. © 2016 American Institute of Chemical Engineers AIChE J, 63: 1236–1245, 2017